(untitled) (Eurasian Research Bulletin, 2023)
During the acute stage of burn injury in the burned, there were changes in the myocardial blood supply of a commonnor focal nature.Various types of rhythm and conduction disturbance that we associate with generaliazed pathophysiological disordes in the acute stage of burn injure, leading to damage to the structure and function of myocardial cells.